2019
DOI: 10.3390/foods8080299
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cooking Quality, Nutritional and Texture Characteristics of Pasta Added with Oat Bran and Apple Flour

Abstract: This study reports the effect of the addition of oat bran and apple flour on the cooking quality, digestibility, antioxidant, nutritional and texture characteristics of a spaghetti-type pasta. Pasta samples were prepared by substituting 50% of durum wheat semolina with oat bran (OBP) or apple flour (AFP). AFP presented higher cooking loss and water absorption index than the control pasta prepared with 100% durum wheat semolina (WSP). The supplementation of pasta with oat bran increased the total dietary fiber … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 37 publications
8
37
0
Order By: Relevance
“…The whole unripe apples ‘Golden Delicious’ without non-edible parts (seeds and peduncle) were used to obtain apple flour by convection drying at 50 °C for 4 h [ 148 ]. Grounded dried pieces were used for making spaghetti-type pasta by replacing 50% of durum wheat semolina with oat bran in order to monitor cooking quality, digestibility, antioxidant, nutritional, and texture characteristics.…”
Section: The Perspective and Development Of Apple-based Functional Products Behind Functional Ingredientsmentioning
confidence: 99%
See 1 more Smart Citation
“…The whole unripe apples ‘Golden Delicious’ without non-edible parts (seeds and peduncle) were used to obtain apple flour by convection drying at 50 °C for 4 h [ 148 ]. Grounded dried pieces were used for making spaghetti-type pasta by replacing 50% of durum wheat semolina with oat bran in order to monitor cooking quality, digestibility, antioxidant, nutritional, and texture characteristics.…”
Section: The Perspective and Development Of Apple-based Functional Products Behind Functional Ingredientsmentioning
confidence: 99%
“…The cooked pasta with apple flour showed the higher content of total phenols and scavenging capacity in comparison with the control samples. Based on the good retention of bioactive compounds and antioxidant capacity after the cooking process of the noodles, the authors concluded that apple flour could be considered as a sustainable food ingredient for the development of a functional food [ 148 ]. In addition, apple pomace water extract could also be considered as a very valuable ingredient for the supplementation or development of fortified foods such as functional yogurt formulations [ 149 ].…”
Section: The Perspective and Development Of Apple-based Functional Products Behind Functional Ingredientsmentioning
confidence: 99%
“…The offer of whole grains on the market is growing; however, there is still a huge gap between recommended levels of dietary fiber intake and its consumption. Hence, improving various products, including pasta, through the addition of dietary fiber has been pursued in recent years [ 11 , 12 , 13 , 25 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, improving pasta through the addition of dietary fiber has been pursued in recent years [ 1 , 9 , 10 , 11 , 12 , 13 ]. Oat bran can be used to provide foods with functional properties [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation